The Semantic Values of Arabic Sounds - Manal Najjar (My University, 2010)
This study aims at establishing a pragmatic and phonetic reading for any creative discourse, written or spoken, in which the findings of modern phonetics are employed. The study argues that applying this type of pragmatic reading by critics or readers will provide a clearer understanding or interpreting leaving space for greater appreciation of its beauty and artistic value which most of Arabs' works enjoy. Old Arabic scholars took into consideration the remarkable effect of the phonetic representations of Arabic alphabet in the understanding of meaning expressed or implied. The sound is felt to generate meaning and to evoke a sense of tasteful ecstasy in heart and soul. Furthermore, the fact of establishing a relationship between the phonetic level with the pragmatic level makes our phonetic theory for any discourse, written or spoken, more realistic, objective and scientific. This research, moreover, examines and argues the studies of contemporary scholars and their attempts to find out new meanings of the sounds of Arabic Alphabet in addition to applying them to poetry.

إن مرادنا الذي نرسمه في هذه الدراسة هو تأسيس قراءة: صوتية دلالية لأي نص إبداعي أو خطابي، قراءة تستثمر نتائج علم الأصوات الحديث وتوظيفها في ضوء هذه القراءة؛ فلا بد أن يحرص الناقد أو القارئ على مثل هذه القراءة للعمل الأدبي إذا أراد أن يكوّن رؤى صحيحة له، وإذا أراد أن يعيش لذتها ويحظى بها، وذلك لأنّ أكثر كلام العرب عليها - وإن كان غُفلا مَسْهُوّاً عنها - فأهل العربية القدامى رأوا أن المادة الصوتية في الحروف العربية لها أثر في استدعاء المعنى أو الإيماء به. واستدعاء مشاعر خفية وصور مُدّخرة وخطرات خيال؛ فكأنك تحس بما يُولّده الصوت من معنى، وبما يبعثه من لذة في النفوس والقلوب. ثم إنّ ربط المستوى الصوتي بالمستوى السياقي والمقامي، يجعل نظرتنا الصوتية لأي خطاب أو نص أكثر واقعية وموضوعية وعلمية. وتكفّلت الدراسة بمقولات الدارسين المعاصرين ومحاولاتهم في الخروج بمعانٍ جديدة لأصوات الحروف العربية، ومحاولة تطبيقها في النص الشعري، ومحاورة تلك المحاولات.
القيم الدلالية لأصوات الحروف في العربية عَوْد على بَدْء